Development of sandwich dot-ELISA for specific detection of Ochratoxin A and its application on to contaminated cereal grains originating from India - Venkataramana, M.; Rashmi, R.; Uppalapati, Siva R.; Chandranayaka, S.; Balakrishna, K.; Radhika, M.; Gupta, Vijai K.; Batra, H. V. (Frontiers in Microbiology, 2015)
In the present study, generation and characterization of a highly specific monoclonal antibody (mAb) against Ochratoxin A (OTA) was undertaken. The generated mAb was further used to develop a simple, fast and sensitive sandwich dot-ELISA (s-dot ELISA) method for detection of OTA from contaminated food grain samples. The LOD (limit of detetion) of the developed ELISA method was determined as 5.0 ng/mL of OTA. Developed method was more specific towards OTA and no cross reactivity was observed with the other tested mycotoxins such as deoxynivalenol, fumonisin B1 or aﬂatoxin B1. To assess the utility and reliability of the developed method, several field samples of maize, wheat and rice (n=195) collected from different geographical regions of southern Karnataka region of India were evaluated for the OTA occurrence. Seventy two out of 195 samples (19 maize, 38 wheat and 15 rice) were found to be contaminated by OTA by s-dot ELISA. The assay results were further co-evaluated with conventional analytical HPLC method. Results of the s-dot ELISA are in concordance with HPLC except for 3 samples that were negative for OTA presence by s-dot ELISA but found positive by HPLC. Although positive by HPLC, the amount of OTA in the three samples was found to be lesser than the accepted levels (>5 µg/kg) of OTA presence in cereals. Therefore, in conclusion, the developed s-dot ELISA is a better alternative for routine cereal based food and feed analysis in diagnostic labs to check the presence of OTA over existing conventional culture based, tedious analytical methods.